To what extent do pre-entry attributes predict first year student academic performance in the South African context? - van Zyl, A; Gravett, S; de Bruin, GP (South African Journal of Higher Education, 2016)
This article reports the results of an investigation into the predictive value of 33 pre-entry attributes, divided into six broad categories, for predicting the academic performance of first year students at an urban South African university. Low levels of student success are a salient problem in South African higher education. Students tend to dropout quickly, quietly and for a range of different reasons. An important part of early interventions is to be able to accurately identify students who are more likely to drop out. Tinto’s longitudinal interactionist theory postulates that pre-entry attributes are the most important influence on a student’s ability to achieve their initial integration during their entry into higher education. In this study, the chi-square test is used to examine the relations between pre-entry attributes and student academic performance. The null-hypothesis of no relationship was rejected for the majority of the predictors, which confirms the importance of pre-entry attributes in the South African academic context.